Fasudil hydrochloride and ozagrel sodium combination therapy for patients with aneurysmal subarachnoid hemorrhage: a cross-sectional study using a nationwide inpatient database - Hiroshi Magara; Takuaki Tani; Shinobu Imai; Anna Kiyomi; Kiyohide Fushimi; Munetoshi Sugiura (BMC, 2024)
Abstract Background Fasudil and ozagrel are drugs with the same indications for the treatment of cerebral vasospasm in Japan. However, there have been no definitive conclusions on the clinical efficacy of fasudil hydrochloride and ozagrel sodium monotherapy or their combination. Therefore, we aimed to investigate the effectiveness of the combined administration of fasudil hydrochloride and ozagrel sodium in Japanese patients with subarachnoid hemorrhage (SAH). Methods This cross-sectional study used Diagnosis Procedure Combination data to assess patients who were hospitalized with SAH and received fasudil hydrochloride or ozagrel sodium between April 2016 and March 2020 (n = 17,346). The participants were divided into three groups based on the treatment received: fasudil hydrochloride monotherapy (F group, n = 10,484), ozagrel sodium monotherapy (O group, n = 465), and fasudil hydrochloride and ozagrel sodium combination therapy (FO group, n = 6,397). The primary outcome was in-hospital mortality. Multivariable adjusted logistic regression analysis (significance level, 5%) was used for data analyses. Results The results of the multivariable analysis, adjusted for factors considered to impact prognosis, showed that the adjusted odds ratio (OR) with the F group as the reference for in-hospital mortality was 0.94 in the FO group (95% confidence interval [CI]: 0.81-1.08, p = 0.355), with no differences compared to the F group. Conclusion Fasudil hydrochloride and ozagrel sodium had different mechanisms of action, suggesting a synergistic effect of combination therapy. However, a comparison of fasudil hydrochloride monotherapy and combination therapy of fasudil hydrochloride and ozagrel sodium showed no difference in the prognostic effect. Therefore, it was suggested that fasudil hydrochloride monotherapy may be sufficient.